Using South African food companies’ nutrition strategies and consumer knowledge, attitudes and practices pertaining to nutrition information, to develop guidelines for the promotion of the prevention of chronic diseases of lifestyle - Kriek, Louise (Stellenbosch : University Stellenbosch, 2010)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2009.